CORRELATION BETWEEN ULTRASONOGRAPHIC FEATURES AND HISTOPATHOLOGICAL FINDINGS OF BREAST LESIONS IN BIOPSIES - Silva, Laila Carolline Freitas e; Furtado, Josmara Ximenes Andrade (Mastology, 2017)
Imaging exams are fundamental tools to characterize palpable lesions and to early detect those not identified on the physical examination. However, the correct interpretation of these findings should be done by correlating them with the probable histological diagnosis of the lesion, and performing the appropriate treatment in a timely manner. The Breast Imaging-Reporting and Data System (BIRADS®) is the system used for this association, which characterizes the findings in mammography, ultrasonography and mammary magnetic resonance images, classifying them according to the probability of malignancy. Objective: To correlate imaging features of breast nodules, evidenced by ultrasonography and classified according to BIRADS®, with the histopathological examination results of material obtained through thick needle biopsy of patients from the mastology ambulatory of the Maternity School Assis Chateaubriand that confirm this predictive value of the imaging examination and the impact on surgical indications. Results: We analyzed 110 patient’s medical records that fit the inclusion criteria and found that more than 97% of lesions with low suspicion of malignancy, BIRADS® 4A, presented a benign histopathological result. However, all patients with images of nodules with high suspicion of malignancy had histopathological diagnosis of invasive carcinoma. In conclusion, the ultrasonographic features of breast lesions have high predictive value in the final diagnosis of the lesion, supporting the decision of conduct in adequate time in each situation.